Comparison of the risk of gastrointestinal perforation between patients with and without rheumatoid arthritis: A nationwide cohort study in Asia - Chang, Ting-Chia; Kan, Wei-Chih; Cheng, Kuo-Chen; Ho, Chung-Han; Chen, Yi-Chen; Chu, Chin-Chen; Hsu, Chien-Chin; Kuo, Hsing-Tao; Lin, Hung-Jung; Huang, Chien-Cheng (Frontiers in Medicine, 2022)
Objectives Patients with rheumatoid arthritis (RA) may have an increased risk for gastrointestinal perforation (GIP) caused by medications or chronic inflammation. However, the risk of GIP between patients with and without RA remains unclear. Therefore, we conducted this study to clarify it. Methods Using the Taiwan National Health Insurance Research Database, we identified patients with and without RA matched at 1:1 ratio by age, sex, and index date between 2000 and 2013 for this study. Comparison of the risk of GIP between the two cohorts was performed by following up until 2014 using Cox proportional hazard regression analyses. Results In total, 11,666 patients with RA and an identical number of patients without RA were identified for this study. The mean age (±standard deviation) and female ratio were 55.3 (±15.2) years and 67.6% in both cohorts. Patients with RA had a trend of increased risk for GIP than patients without RA after adjusting for underlying comorbidities, medications, and monthly income [adjusted hazard ratio (AHR) 1.42; 95% confidence interval (CI) 0.99–2.04, p = 0.055]. Stratified analyses showed that the increased risk was significant in the female population (AHR 2.06; 95% CI 1.24–3.42, p = 0.005). Older age, malignancy, chronic obstructive pulmonary disease, and alcohol abuse were independent predictors of GIP; however, NSAIDs, systemic steroids, and DMARDs were not. Conclusion RA may increase the risk of GIP, particularly in female patients. More attention should be paid in female population and those with independent predictors above for prevention of GIP.